Diseño y creación de trampas para las moscas stomoxys calcitrans y haematobia (lyperosia) irritans que afectan los bovinos en Tenjo, Cundinamarca por medio de la utilización de atrayentes de origen natural – estudio experimental - Llanos Blanco, Christian Camilo; Benavides Melo, Lizeth Dayany (Universidad Antonio Nariño, 2022)
We are facing a situation of injury to the welfare of bovines due to cause of the proliferation of flies (Stomoxys calcitrans and Lyperosia irritans), which has become a real problem and challenge for those in charge of cattle care (workers and veterinarians). Different have been used methods of prevention and control of fly populations, however remains a serious animal health problem, affecting the development and production of the animals and clearly their health.